NEURODEVELOPMENTAL CARE OF PRETERM BABIES AND ITS KEY ELEMENTS - Sarapuk, I. M.; Pavlyshyn, H. A.; Lacina, L.; Królak-Olejnik, B. (International Journal of Medicine and Medical Research, 2017)
Over the past few decades, the advancements in the perinatal and neonatal intensive care have led to a significant survival of premature infants. However neurodevelopmental outcome still remains the topical issues of concern. Developmental care is an approach that is aimed to reduce the mismatches between extra- and intra-uterine environments, decrease the stress of preterm newborns in neonative intensive care units, and thus promote optimal neurobehavioral development of the infant. The Newborn Individualized Developmental Care and Assessment Program (NIDCAP) model was developed as a clinical framework for the implementation of developmental care. The model focuses on detailed reading of each individual infant’s behavioral cues. By observing the child during the routine manipulation performance (before, during and after) and a detailed description of his/her behavioral responses, a professional can assess the ability of the infant’s immature nervous system to tolerate the environment and care manipulations. Such evaluation will enable to determine the adequacy of environmental conditions and care manipulations to baby’s opportunities and needs, with their subsequent correction and adaptation. NIDCAP’s aim is to support the child in its increasing tolerance to stimuli and to minimize stressful events and manipulation. With the help of NIDCAP approaches in neonatal care, medical staff study how to read infants’ behavior, hear their voice and understand them.